Metadata Securing Approach on Ubiquitous Computing Devices with an Optimized Blockchain Model - Ayyasamy, S. (Journal of Ubiquitous Computing and Communication Technologies, 2022)
Metadata is an exploration of the given data. It organizes the data by grouping the collected information on a particular structure for easy understanding. Metadata reduces the computational burden on data mining algorithms by keeping an organized record. Data that are related to healthcare application requires serious attention on privacy concern and therefore such information are encrypted in most cases. Processing of encrypted data is difficult, and it may lead to estimate the prediction with a faulty output. Hence, a blockchain based data securing system is proposed in the work for securing the data that are transmitted from a ubiquitous computing device. The paper also incorporates the proposed work with a whale optimization algorithm for reducing the execution time required on the blockchain based data storage and retrieval process.
Keywords: Pervasive computing; metadata privacy; wearable devices; smart healthcare measurement; blockchain iteration; whale optimization